Asymmetric hydrogenation of 2, 3-dihydro-1H-inden-1-one oxime and derivatives. Issue 6 (1st April 2016) - Maj, Anna M.; Suisse, Isabelle; Agbossou-Niedercorn, Francine
Graphical abstract: Abstract: Asymmetric hydrogenation of 2, 3-dihydro-1 H -inden-1-one oxime and derivatives to produce the corresponding optically active amine has been performed in the presence of rhodium and iridium catalysts. The optimization of neutral rhodium based catalytic systems by varying the operating conditions and the ligand around the metallic centre led to high conversions with moderate enantiomeric excesses.